How nanotechnology can enhance docetaxel therapy - Zhang L (Dove Medical Press, 2013)
Li Zhang, Na ZhangSchool of Pharmaceutical Science, Shandong University, Shandong Province, People's Republic of ChinaAbstract: Docetaxel has been recognized as one of the most efficient anticancer drugs over the past decade; however, its poor water solubility and systemic toxicity have greatly limited its clinical application. In recent decades, the emergence of nanotechnology has provided new drug delivery systems for docetaxel, which can improve its water solubility, minimize the side effects and increase the tumor-targeting distribution by passive or active targeting. This review focuses on the research progress in nanoformulations related to docetaxel delivery – such as polymer-based, lipid-based, and lipid-polymer hybrid nanocarriers, as well as inorganic nanoparticles – addressing their structures, characteristics, preparation, physicochemical properties, methods by which drugs are loaded into them, and their in vitro and in vivo efficacies. Further, the targeted ligands used in the docetaxel nanoformulations, such as monoclonal antibodies, peptides, folic acid, transferrin, aptamers and hyaluronic acid, are described. The issues to overcome before docetaxel nanoformulations can be used in clinical and commercial applications are also discussed.Keywords: docetaxel, nanotechnology, nanoformulations, target delivery systems, cancer therapy